Final answer:
To solve the equation ax - y = bx for x, add y to both sides, combine x terms, factor x out, and divide by (a - b) resulting in the solution x = y / (a - b).
Step-by-step explanation:
To solve the given equation ax - y = bx for x, we aim to isolate x on one side of the equation:
First, we add y to both sides of the equation: ax = bx + y.
Next, we group the x terms together: ax - bx = y.
Then, we factor out x: x(a - b) = y.
Finally, we divide both sides by (a - b) to solve for x: x = y / (a - b).
So, the solution is x = y / (a - b).